Short and long-term follow-up after coronary artery bypass surgery or percutaneous coronary intervention among elderly patients with multivessel disease (Annals of Medical Research, 2021)
Aim: Compared to young patients, elderly patients are more prone to multivessel coronary artery disease, have more calcific coronary vessels, and experience greater delays in receiving medical help. Notably, differences in in-hospital and post-discharge mortality and morbidity rates have been observed between patient who underwent percutaneous coronary intervention (PCI) and coronary artery bypass graft (CABG). The present study primarily aimed to determine differences between CABG and PCI (with new-generation drug-eluting stents) among elderly patients with unstable angina pectoris (USAP) or non-ST segment elevation myocardial infarction (NSTEMI) and intermediate SYNTAX score.Materials and Methods: This study evaluated the 441 consecutive elderly patients with with USAP or NSTEMI divided into two groups as PCI or CABG were retrospectively evaluated and followed up for 30 days and 5 years. All clinical incidents, such as all-cause mortality, cardiac death, myocardial infarction (MI),stroke, revascularization and stent thrombosis were recorded.Results: Among the include patients, 200 received PCI (%45.4) and 241 (%54.6) received CABG. 1.3% and 4.8% of the patients in the PCI and CABG group developed a stroke, respectively (p=0.048). The PCI group (23%) exhibited a higher major adverse cardiovascular events percentage than the CABG group (18.7%), albeit not significantly (p=0.264). Repeat revascularization was required in 20 (10.1%) and 18 patients (10.8%) in the PCI and CABG group, respectively (p = 0.337). Among the included patients, 10.3% of those who underwent PCI developed MI, whereas only of 5.3% of those who underwent CABG developed the same (p=0.045). All-cause mortality rates at the 5-year follow-up were 12.7% (25 patients) and 9.1% (21 patients) in the PCI and CABG group, respectively (p=0.225). Accordingly, no difference in all-cause mortality between both groups was found during the first 30 days following revascularization (p=0.13). Moreover, Kaplan–Meier survival analysis showed a difference between PCI and CABG during the 5-year observation period.Conclusion: No difference in all-cause mortality and repeat revascularization over a 5-year follow-up period was observed between the PCI and CABG groups. However, the CABG group had higher stroke rates, whereas the PCI group had higher MI rates.
Keywords: Acute coronary syndrome; coronary artery bypass graft; elderly patients; percutaneous coronary intervention